Uses and gratification of WhatsApp Meta for Academic and Social Life of Fountain University, Osogbo Students (Journal of Management and Social Sciences, 2026)
This study explores the uses and gratifications of WhatsApp among Fountain University students, focusing on how they utilise the platform to meet their cognitive, social integrative, affective, and tension-release needs. Leveraging the Uses and Gratifications Theory, this research investigates the role of WhatsApp in facilitating academic collaboration, social interaction, and information sharing among students. Findings suggest that students predominantly use WhatsApp for social integrative needs, such as staying connected with friends and family, and cognitive needs, like sharing study materials and discussing coursework. The study highlights the significance of WhatsApp in enhancing students' academic experiences, social connections, and collaborative learning. Results also indicate that students' perceived usefulness, and ease of use of WhatsApp influence their adoption behaviour, underscoring the platform's potential as a teaching supplement. This research provides insights into the impact of social media on students' academic and social lives, offering implications for educators and policymakers seeking to integrate technology into university education.Keywords:Uses and gratification, Meta AI, communication platforms, academic support